In Vivo Tracking of EGFP-Labeled Mesenchymal Stem Cells Through Live Animal Imaging - Fabin (American Journal of Translational Medicine, 2020)
Cell therapy transplants living cells into target tissues or injury sites, inducing therapeutic effects in diseased tissues or organs. In order to determine the survival and differentiation of transplanted stem cells in vivo and improve their therapeutic efficacy, we developed a non-invasive labeling technique to track transplanted mesenchymal stem cells in living animals. In this study, we used electroporation to transfect the pCMVEGFP (enhanced green fluorescent protein) plasmid into human cells, generating EGFP-labelled umbilical cord-derived mesenchymal stem cells (UC-MSCs) in vitro. The EGFP-labeled UC-MSCs were then subcutaneously injected into nude mice and were tracked for 5 weeks using the IVIS live animal imaging system. We found that the EGFP transfection efficiency reached 81% in EGFP-labeled UC-MSCs. In vivo imaging analysis showed that the EGFP-labeled cells retained strong fluorescence expression for 7 days and then gradually decreased over time. However, an immunohistochemistry analysis indicated that transplanted cells could survive for more than 6 months in vivo. In conclusion, EGFP-labeling is a valuable technique for tracking the survival and migration of transplanted stem cells in vivo, leading to new understandings of the molecular mechanisms of cell therapy. (Am J Transl Med 2020. 4:205-215).